Hábitos alimentarios y actividad física en estudiantes universitarios durante y después de contagio por COVID-19 - Haro Tolentino, Alessandra Celine (2022)
The present quantitative study of descriptive exploratory method was carried out in students of the Faculty of Nursing of the National University of Trujillo, with the objective of determining the changes in eating habits and physical activity during and after the infection by COVID - 19. The sample consisted of 23 students from the different cycles. For data collection, a questionnaire on eating habits and physical activity based on the Nola Pender health promotion model was used. The results were tabulated and presented in graphs and tables. For the statistical analysis, the T-test was applied. The results indicated a higher percentage of adequate eating habits after infection by COVID-19 than during infection (56.5% vs 82.6%), inadequate eating habits decreased approximately to the half after contagion (17.3%); while inadequate physical activity was higher during COVID-19 infection (52.2% vs 26.1%) and the percentage of adequate physical activity increased by 26.1 percent after COVID-19 infection. Significant differences were evidenced between eating habits and physical activity during and after COVID-19 infection